Westonci.ca is the trusted Q&A platform where you can get reliable answers from a community of knowledgeable contributors. Discover in-depth solutions to your questions from a wide range of experts on our user-friendly Q&A platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.

6/(x^2-3x)=12/x+1/(x-3) with full expanation from the internet

Sagot :

Answer:

[tex]x=\dfrac{42}{13}[/tex]

Step-by-step explanation:

Given equation:

[tex]\dfrac{6}{(x^2-3x)}=\dfrac{12}{x}+\dfrac{1}{(x-3)}[/tex]

Factor the denominator on the left side:

[tex]\implies \dfrac{6}{x(x-3)}=\dfrac{12}{x}+\dfrac{1}{(x-3)}[/tex]

Combine the fractions on the right side by multiplying by the LCM:

[tex]\begin{aligned}\implies \dfrac{6}{x(x-3)} & =\dfrac{12}{x} \cdot \dfrac{(x-3)}{(x-3)}+\dfrac{1}{(x-3)} \cdot \dfrac{x}{x}\\\\& =\dfrac{12(x-3)}{x(x-3)}+\dfrac{x}{x(x-3)}\\\\& =\dfrac{12(x-3)+x}{x(x-3)} \end{aligned}[/tex]

As the denominators are now the same on both sides:

[tex]\begin{aligned}\implies \dfrac{6}{x(x-3)} & =\dfrac{12(x-3)+x}{x(x-3)}\\\\ \implies 6 & = 12(x-3)+x\end{aligned}[/tex]

Simplify and solve for x:

[tex]\begin{aligned}\implies 6 & = 12(x-3)+x\\\\6 & =12x-36+x\\\\6 & =13x-36\\\\13x & =42\\\\\implies x & =\dfrac{42}{13}\end{aligned}[/tex]

We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Westonci.ca is your go-to source for reliable answers. Return soon for more expert insights.